Labour market relevant migration policy - Thomas Straubhaar (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2006)
In late 2005 the Commission of the European Communities has presented a policy plan on legal migration including admission procedures capable of responding promptly to fluctuating demands for migrant labour. The EU migration policy plan stresses the importance of having a coherent agreement on common EU migration rules and actions among the member states. The following paper gives some guidelines for a labour market relevant European Migration Policy (EMP). According to the view of the EU commission it looks at both sides the internal migration and the inflow of foreigners to the EU. Furthermore, it is not limited to the issue of admission of immigrants. It also addresses questions of stay and work and the aspects of illegal migration. The objective of the paper is to formulate a coherent conceptual EMP in order to ensure an efficient management of migration flows both toward and inside Europe.
Keywords: 330; Wanderungspolitik; Einwanderungspolitik; Arbeitsmigration; Aufenthaltsrecht; illegale Einwanderung; Saisonarbeit; internationale Wanderung; Binnenwanderung; Einwanderer; europäische Integration; Integrationspolitik; Europäische Union